2018
DOI: 10.1159/000491802
|View full text |Cite
|
Sign up to set email alerts
|

An Interstitial 17q11.2 de novo Deletion Involving the CDK5R1 Gene in a High-Functioning Autistic Patient

Abstract: We describe a 32-year-old male patient diagnosed with high-functioning autism spectrum disorder carrying a de novo 196-kb interstitial deletion at chromosome 17q11.2. The deletion was detected by array CGH (180K Agilent) and confirmed by quantitative PCR on genomic DNA. The deleted region spans the entire PSMD11 and CDK5R1 genes and partially the MYO1D gene. The CDK5R1 gene encodes for a regulatory subunit of the cyclin-dependent kinase 5 responsible for its brain-specific activation. This gene has been previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Cyclin-dependent kinase 5 (CDK5) is a unique member of the cyclin-dependent kinases (Cdks) family of serine/ threonine kinases [6], CDK5 not only plays an important regulatory role in the physiological and pathological processes of the nervous system, but also regulates cell apoptosis and senescence, and works in a variety of tumors [7][8][9]. Recent studies have found that CDK5 has the effect of driving G1-S and RB phosphorylation in medullary thyroid carcinoma models [10].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclin-dependent kinase 5 (CDK5) is a unique member of the cyclin-dependent kinases (Cdks) family of serine/ threonine kinases [6], CDK5 not only plays an important regulatory role in the physiological and pathological processes of the nervous system, but also regulates cell apoptosis and senescence, and works in a variety of tumors [7][8][9]. Recent studies have found that CDK5 has the effect of driving G1-S and RB phosphorylation in medullary thyroid carcinoma models [10].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, cell cycle, pyrimidine metabolism, DNA replication, p53 signaling pathway, ubiquitin-mediated proteolysis, and the TCA cycle might be key pathways in E2F2's involvement in the initiation and progression of HCC. E2F2 can be regulated by various traditional Chinese medicine components, suggesting new approaches in the treatment of liver cancer with traditional Chinese medicine [20][21][22][23][24][25][26][27][28][29][30].…”
Section: In the Exploration Of New Biomarkers And Targetsmentioning
confidence: 99%
“…GSEA found that the Notch signaling pathway and non-small cell lung cancer were significantly enriched in high CDK5R1 expression phenotypes. It is believed that elevated CDK5R1 could be a promising independent prognostic factor for poor survival in HCC, providing a new candidate for the prognostic assessment scibasejournals.org Han R of HCC [21][22][23][24][25][26][27][28][29][30].…”
Section: In the Exploration Of New Biomarkers And Targetsmentioning
confidence: 99%